UTILIZING WHATSAPP API FOR SCHOOL PAYMENT SYSTEM IMPLEMENTATION WITH CODEIGNITER - Indra Ava Dianta; Agustinus Budi Santoso; Muh Sabiq (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
SDIT NIDAUL HIKMAH SALATIGA is a private school with more than 600 students. Despite the large number of students, administrative services are still manually performed, including writing and compiling payment receipts in Microsoft Excel, manual data retrieval, and printing invoices from Excel. This method is not only impractical and inefficient but also often leads to calculation discrepancies. This study aims to develop an information system using the CodeIgniter framework. CodeIgniter, with its Model, View, Controller (MVC) concept, provides ease in designing information systems. The implementation of the WhatsApp API aims to create an up-to-date system by introducing WhatsApp notification features containing detailed billing and transaction information to parents/guardians of students. The research also aims to design a practical and effective information system in school administration services, making it easier and faster to perform administrative tasks. Through validation conducted by experts and users, it can be concluded that this system has received excellent ratings and can be applied as a tool for school administrative payment services, with revisions made if any issues are found. User Acceptance Testing (UAT) was conducted on sample respondents by asking users to try accessing the system and provide feedback by completing the provided questionnaire. From the test results, respondents gave a total score of 90% for ease of use, 86% for appearance, and 91% for functionality, indicating that users strongly agree that this school payment information system is easy to operate, has comprehensive features, and facilitates administrative services.